De l'attrait des médias sociaux pour l'apprentissage des langues – Regard sur l'état de l'art - Katerina Zourou (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This paper sets the stage for the articles selected for the special issue "language learning and social media: (r)evolution?". Starting with some definitions of mainstream terms like "social media", "web 2.0", "social web", "social networking sites (SNS)" and "web 2.0 language learning communities". The purpose is not to "reinvent the wheel" by suggesting new definitions, but to synthesize definitions of mainstream terms and juxtapose them to similar concepts from CALL literature. We then critically discuss three key features of web 2.0 technologies (user participation, openness and network effects). Despite the fact that these three features were present to some extent in technologies prior to social media, we examine whether they take on a radically different meaning in the social media era. Research insights are discussed in the last section of the paper.